A escola moderna no Brasil e as contribuições de Lauro de Oliveira Lima: avanços e contradições - Silveira, Poliana Oliveira (2019)
The present work is in line with the research history and historiography of education aiming to know the pedagogical thinking of educator Lauro de Oliveira Lima (1921 -2013). The defined historical period for the research is among the decades of 1960 and 1970, time in that the more educator contributed to the education in the country, with more than 30 publications regarding the education. We tried to analyze and understand the challenges of Lauro de Oliveira Lima before the longings of the education in the proposed period, as well as his reflection on the impasses and reforms in the education. We confronted ourselves with countless conflicts and challenges lived in the bibliographical researches, we found works of different slopes of the author's pedagogic thought and a great amount of works to be known. Another challenge is the absence of studies regarding her thought. The objective of this work is to know the life and the pedagogic conception of Lauro de Oliveira Lima, that a pioneer was made in the studies psychogenetic the Jean Piaget. We emphasized that the sustentation of the present ideas here occurs of readings based in the history of the education, in the Pedagogic Thought and in the studies on intellectuals in Brazil. For elaboration and sustentation of this work, we looked of authors that problematized the historical context and the author’s production. We intend to analyze the work the Modern High school: Organizations, Methods and Processes, produced in the decade of 1960, that it illustrates his pedagogic thought and the structural subjects of the education, proposing a new education model to be proceeded. The work suggests linked subjects to the perspectives politics, ideological, methodological, of school organization and of teaching processes. Therefore it was made an analysis of the work considering contribution and changes for the Brazilian education in the studied period. The analysis of the work also in the group to the understanding of the author's Pedagogic Thought. About the results we note the author's contradictions, adapts to produce the time he is living, adapts to the technical discourse, professionalization and institutionalization, he started offering courses for teachers with technical bias.